1982
DOI: 10.1007/bf00361366
|View full text |Cite
|
Sign up to set email alerts
|

Wormian bones in osteogenesis imperfecta and other disorders

Abstract: When are Wormian bones significant is not an easy question to answer, but its relevance is important in relation to bone dysplasias such as osteogenesis imperfecta. Recognition will differ with age of patient, radiographic objectivity, and personal subjectivity. In order to attempt an answer, the skull radiographs of 81 cases of osteogenesis imperfecta of varying ages were examined for the presence of Wormian bones. These were compared against the incidence of Wormian bones in 500 skull radiographs of normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
12

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 13 publications
2
51
0
12
Order By: Relevance
“…La taille élargie des sutures, et les formations de type os wormiens semblent témoi-gner de la capacité d'adaptation réduite des os de la voûte crânienne à suivre la croissance de la masse neurale [7,13]. La base du crâne et le condyle mandibulaire sont d'origine enchondrale comme les os longs.…”
Section: Relation Génotype-phénotypeunclassified
“…La taille élargie des sutures, et les formations de type os wormiens semblent témoi-gner de la capacité d'adaptation réduite des os de la voûte crânienne à suivre la croissance de la masse neurale [7,13]. La base du crâne et le condyle mandibulaire sont d'origine enchondrale comme les os longs.…”
Section: Relation Génotype-phénotypeunclassified
“…5 These showed characteristic features of generalized osteopenia, abnormal thinning of cortical bone, and the presence of multiple small bone islands within cranial suture lines (Wormian bones). 6,7 The parents were immediately informed of the revised diagnosis of OI and given full access to the baby.…”
Section: Case Reportmentioning
confidence: 99%
“…
both the retina and choroid found on angiography added weight to a diagnosis of vasculitis, particularly giant cell arteritis, 6 and led to a temporal artery biopsy. Clinical suspicion was confirmed with a positive biopsy, despite both normal ESR and CRP.
…”
mentioning
confidence: 99%
“…1,4 Basilar invagination, a clinical manifestation, may cause cranial nerve compression due to odontoid process protrusion through foramen magnum into the intracranial cavity. 5,6 The trigeminal nerve may be involved, resulting in neuralgic pain, often refractory to drug treatment. Other possible pathogeneses include arachnoid adhesions and increased vascularization in the foramen magnum area.…”
Section: Introductionmentioning
confidence: 99%
“…Normal anatomical relations are distorted by bone deformity and the lower surface of the foramen ovale may be posteromedially displaced, thus making the conventional route for percutaneous approaches virtually impossible to use. 5,7,8 The authors found that Mayfield clamps, necessary in the previous alternatives, also imply high complication risk given the potential fragmentation of wormian bones and deformity worsening. In cases of OI, cannulation of the foramen ovale and classical percutaneous treatment can be a useful, safe and efficient alternative using CT-guided puncture for patients with trigeminal neuralgia and other bone deforming diseases that severely affect the skull base.…”
Section: Introductionmentioning
confidence: 99%